Empowering Leadership: A Journey of Growth and Insight Through a Mentoring Program for Nurses in Leadership Positions - Lysfjord EM; Skarstein S (Dove Medical Press, 2024)
Else Marie Lysfjord,1 Siv Skarstein2 1Faculty of Nursing and Health Sciences, North University, Namsos, Norway; 2Department of Nursing and Health Promotion, Oslo Metropolitan University, Oslo, NorwayCorrespondence: Else Marie Lysfjord, Email else.m.juul@nord.noAim: This study explores the experiences of mentors and mentees participating in a mentor program for nurses in leadership positions, aiming to identify areas for program improvement.Design and Methods: A qualitative approach was used, with semi-structured interviews conducted with 20 nurses in leadership roles. The participants, 10 mentees and 10 mentors, were involved in the Norwegian Nurses Organization's "Mentor Program for Nurses as Leaders". Thematic analysis was applied to the data.Results: Participants in the mentorship program reported increased leadership awareness, stronger motivation, better stress-coping mechanisms, and greater confidence as leaders. They received valuable feedback and support from their mentors, boosting their motivation to pursue leadership roles. Both mentees and mentors expressed a desire for a longer program and emphasized the importance of networking opportunities, along with the need for predictability and long-term planning to improve program effectiveness.Conclusion: Participants reported that the mentorship program increased their awareness, motivation, coping skills, and confidence as leaders, encouraging them to pursue leadership roles. The results show that the NNO's mentor program positively influences leadership aspirations of new nurse leaders, with potential for further development in networking and program duration.Keywords: mentoring, nurses, evaluation, leadership, experiences